Behavioural interviewing [ (Video Education Australasia, 2005)
This program explores a relatively new method of job interviewing called behavioral interviewing. Interviews are based on previous experiences of the applicant, combined with scenarios and examples to help predict future behavior. Employers can avoid the potentially nebulous strengths and weaknesses questions in order to focus on actual behaviours exhibited and the way an individual adapts to particular situations